Accelerated point of muscle deoxygenation during the 20‐m shuttle run test. (16th April 2017) - Kume, Daisuke; Iguchi, Akira; Endoh, Hiroshi
Summary: This study examined whether the point of accelerated deoxygenation of active muscle occurs during the 20‐m shuttle run test (20mSRT) and, if so, whether it is associated with exercise performance in the test. Twenty‐nine male subjects performed the 20mSRT, and concentration changes in oxyhaemoglobin (ΔOxy‐Hb) and deoxyhaemoglobin (ΔDeoxy‐Hb) in the m. vastus lateralis were measured using a portable near‐infrared spectroscopy device. The difference between the relative concentration changes in ΔOxy‐Hb and ΔDeoxy‐Hb (Δ[Oxy‐Hb − Deoxy‐Hb]) was regarded as the muscle oxygenation index. Group‐averaged Δ[Oxy‐Hb − Deoxy‐Hb] showed progressive decrease during the test. However, among the individuals, we found an accelerated point of decrease in Δ[Oxy‐Hb − Deoxy‐Hb] in 20 subjects, which revealed that the laps at the accelerated point correlated with the total laps ( r  = 0·78). These results demonstrate that the accelerated deoxygenation of active muscle occurs during the 20mSRT, but not in all cases. Our findings also indicate that if the accelerated point of muscle deoxygenation occurs, the timing of its appearance is related to 20mSRT performance.